“They came there as workers”: Voice, dialogicality and identity construction in textual representations of the 2012 Marikana miner’s strike - Bernard, Taryn (Stellenbosch Papers in Linguistics Plus, 2016)
In August and September 2012, a mineworkers’ strike took place at a mine operated by Lonmin, a British producer of platinum metals, in the Marikana area of the South African platinum belt. The strike received international attention after over 70 Lonmin employees were injured, 34 of whom suffered fatal wounds. Drawing on a social constructivist view of language and discourse, this research critically investigates how social actors are represented in two contrasting text types; namely Lonmin Corporate Social Responsibility (CSR) reports and transcripts of verbal testimonies given at the Marikana Commission of Inquiry. Van Leeuwen’s (2008) socio-semantic categories for the representation of social actors, as well as Bakhtin’s (1981) notions of ‘dialogicality’ and ‘voice’, are incorporated as key methodological tools. A critical analysis of the texts reveals that although the strikes were symbolic acts against a repressive economic and social system, during their testimonies, the mineworkers often adopt the same representational devices used by the corporate actors they are reacting against. Since linguistic and discursive features are representative of ideologies (see Wodak 1989, Wodak 1996, Fairclough 2003 and van Dijk 2006), the research highlights the dominance of neoliberal ideologies in the South African mining industry and comments on the implications this may have for future transformation in this sector.